PEMANFAATAN MATA AIR DUKUH BLAHKIUH UNTUK SISTEM PELAYANAN AIR TERINTEGRASI - Mahesa Adi Wardana, I Gusti Ngurah Kade; Wiwin Andayani, Ketut; Anom Purwa Winaya, I Nyoman (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2024)
Spring water is one of the natural resources that are beneficial to human life such as fulfilling the needs of clean water, irrigation, and others. Non-integrated spring management has the potential to create conflicts among water users, as is the case at Dukuh Blahkiuh Spring. The unbalanced fulfilment of water needs is felt by Subak Uma Poh farmers and other water users. Related to this, it is necessary to analyse the current availability of water and compare it with the needs and potential that can be developed. The utilisation of springs can be properly integrated if the water balance conditions are known in order to achieve fairness and appropriate proportions and avoid conflicts. The method in this research is quantitative analysis with variables of spring discharge, clean water needs, irrigation, and integrated water utilisation systems. This research shows that the potential water availability at Dukuh Blahkiuh Spring currently has an average discharge of 54.53 litres/second with a reliability level of 80%. The water balance condition that occurs is at the water surplus level with a percentage of 38.81%, which means that spring utilisation still has the potential to be developed. The integrated water service system is designed by prioritising the proportion of water use at 47.93% for clean water, 13.26% for irrigation and followed by other uses at 38.81%. Water balance analysis can illustrate the availability, demand and development potential of Dukuh Blahkiuh Spring, so that the integration of management systems can be done to increase its utilisation.Keywords: springs, water balance, water alocation